Shop drawing of DY-10 elevation, section & partial elevation (RF-008_Rev D) - Arman Engineering Ltd. (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of both PDF and DWG version of drawings.